Adenosine dysfunction and adenosine kinase in epileptogenesis - Boison, Detlev (2010)
Traditionally, epilepsy has been considered to be a disorder of neuronal dysfunction. Based on this dogma, drug development efforts have largely focused on neurocentric model systems to screen for compounds that affect the function of neurons. Unfortunately, about 30% of all patients with epilepsy – or more than 20 million worldwide – are refractory to classical neurocentric pharmacotherapy. The failure of neurocentric pharmacotherapy in epilepsy requires radical rethinking and the search for novel therapeutic targets. Research from recent years suggests that epilepsy is a disorder of astrocyte dysfunction. Astrocytes are key regulators of the brain’s own anticonvulsant adenosine. Thus, any dysfunction in astrocyte metabolism will drastically affect the brain’s ability to control excitability via adenosinergic neuromodulation. This review will focus on the astrocyte-based enzyme adenosine kinase (ADK) as the key regulator of synaptic adenosine. Astrogliosis – a pathological hallmark of the epileptic brain – leads to overexpression of the adenosine-removing enzyme ADK and therefore to adenosine deficiency. Evidence from transgenic animals demonstrates that overexpression of ADK per se is sufficient to trigger seizures. Consequently, pharmacological inhibition of ADK is very effective in suppressing seizures that are refractory to classical antiepileptic drugs. The recent definition of ADK as rational target to predict and to prevent seizures in epilepsy has prompted the development of focal adenosine augmentation therapies (AATs) that have been designed to selectively reconstitute adenosinergic signalling within an area of astrogliosis-based adenosine-dysfunction. This therapeutic challenge has experimentally been met with polymeric or stem cell based brain implants to afford the focal delivery of adenosine.